What was the ancestral function of decidual stromal cells? A model for the evolution of eutherian pregnancy. (April 2016) - Chavan, Arun Rajendra; Bhullar, Bhart-Anjan S.; Wagner, Günter P.
Abstract: In human and mouse, decidual stromal cells (DSC) are necessary for the establishment (implantation) and the maintenance of pregnancy by preventing inflammation and the immune rejection of the semi-allograft conceptus. DSC originated along the stem lineage of eutherian mammals, coincidental with the origin of invasive placentation. Surprisingly, in many eutherian lineages decidual cells are lost after the implantation phase of pregnancy, making it unlikely that DSC are necessary for the maintenance of pregnancy in these animals. In order to understand this variation, we review the literature on the fetal-maternal interface in all major eutherian clades Euarchontoglires, Laurasiatheria, Xenarthra and Afrotheria, as well as the literature about the ancestral eutherian species. We conclude that maintaining pregnancy may not be a shared derived function of DSC among all eutherian mammals. Rather, we propose that DSC originated to manage the inflammatory reaction associated with invasive implantation. We envision that this happened in a stem eutherian that had invasive placenta but still a short gestation. We further propose that extended gestation evolved independently in the major eutherian clades explaining why the major lineages of eutherian mammals differ with respect to the mechanisms maintaining pregnancy. Highlights: We review the role of decidual stromal cells in basal eutherian mammals. We suggest that the ancestral function of decidual cells was related to implantation. Extended gestation evolved after the eutherian radiation. The role of decidual cells in the maintenance of pregnancy is a derived feature of euarchontoglires.